Mellom profesjonell og folkelig kunnskap. En kvalitativ studie av helsepersonell sin kunnskap om og håndtering av «læsing» i en norsk-samisk kommune. (December 2014) - Larsen, Anette Langås; Hamran, Torunn; Foss, Nina
Backround: In northern Norway spiritual healing traditions are still practiced, especially among people related to Sami background and culture. Studies indicate that the general public believes that health care professionals are skeptical when it comes to the traditional spiritual healing practice known as "reading" or læsing in Norwegian. Aim: The purpose of this article is to describe health care providers' understanding of the practice of traditional healing and how health care professionals handle it. Methods: A qualitative study based on semi structured interviews and two focus group interviews with 13 primary health care professionals, two physicians, seven nurses and four welfare workers, was conducted in a rural Sami area in North-Norway. Findings: The study shows that health care professionals have great knowledge of and respect for reading. The knowledge is based on the health care personnel's relationships with the community. Health care professionals distinguish between how they relate to reading as private persons and as health care professionals. Conclusion: The analysis provides an understanding of how traditional knowledge and professional biomedical knowledge plays together in health care providers' work in primary health care. It can provide input into the development of a culturally sensitive public health care service.